The Role of Quality Assurance Certification Institutions in Islamic Religious Education - Urwatul Wusqo Nur Salsabila; Siti Julaiha (Al-Qalam Institue, 2026)
The uneven distribution of educational quality in Indonesia remains a serious challenge, particularly due to the inconsistent implementation of the National Education Standards (SNP) across regions. This disparity impacts the quality of learning, including in Islamic Religious Education (PAI), which demands both academic achievement and character building. This study aims to analyze the role of educational quality assurance certification institutions in improving PAI quality through monitoring, coaching, and evaluation mechanisms. The method used was a qualitative study based on a literature review, with data sources consisting of regulations, institutional reports, and national and international scientific publications. The results indicate that certification institutions play a crucial role in ensuring compliance with quality standards, providing mentoring, and strengthening the integration of spiritual values ​​in PAI learning. However, implementation gaps between regions and variations in audit quality were identified that need to be addressed. This study concludes that PAI quality assurance requires a holistic approach encompassing both academic and spiritual aspects. The contribution of this research lies in strengthening educational quality assurance theory and in developing a new understanding of the integration of Islamic values into certification mechanisms.